Replication of microstructured tools for electrochemical machining applications. Issue 1 (January 2016) - Weißhaar, Konstantin; Weinmann, Martin; Jung, Anne; Weber, Olivier; Natter, Harald
Abstract Electrochemical machining (ECM) is a powerful method to machine metals independently of their mechanical properties. Micro-sized structures can be formed with high precision. For this purpose, it is necessary to manufacture tools with adequately fine structures. Conventional ECM tools were manufactured by micro-drilling, -milling, -turning, etc. Depending on the complexity of the structures, these techniques are very elaborate and expensive. Recently, a new procedure, which combines photolithography and electroforming, the so-called PhoGaTool process (photolithographic electroforming of ECM tools), was published. In the present work, we demonstrate how this method can also be used for copying ECM tools that were conventionally manufactured. A copy of an industrial PECM tool (precise electrochemical machining) was manufactured and used for the structural characterization and determination of the replication accuracy. The electroforming parameters like deposition conditions, bath composition as well as physical and chemical parameters were optimized for model systems. The inclusion of bath additives in the metal matrix during the deposition leads to micro-stresses, hence in this contribution, an alternative additive-free electrolyte was used. The accuracy of the process was investigated by means of confocal laser scanning microscopy. Average deviations of the structure depth and the lateral structure dimensions are in the range of 5 %.